Pembuatan Edible Coating dari Tepung Tapioka dan Aplikasinya pada Buah Tomat - Haryati -; Raudah -; Muhammad Sami (Jurnal Teknologi, 2017)
Edible coating is film that can coat and safe food for consumption by means of wrapping, dripping and spraying to provide containment selective displacement of gas, water vapor and solute. This research was conducted to produce an edible coating of stach and applied to tomatoes to get the characteristic of edible coating during storage and the amount of addition of glycerol, cmc, stearic acid and the quality of the product, in order to provides an alternative environmentally friendly packaging. Manufacturing of edible coating was done by dissolving 2 grams of tapioca in 100 ml of distilled water and adding glycerol (10; 15; 20 ml), cmc (1; 2; 3 grams) and stearic acid (0,25; 0,5; 0,75 grams) accordance with the treatment of Respone Surface Methodology. The analysis results of tomatoes in the best edible coating during storage for 1 week cause a weight loss of 11,6448 gr, total acid 3,06102 ml/gr, vitamin C 0,32775 mg/g, and pH value 4,63517. While to analysis results of tomatoes in the best edible coating during storage for 2 week cause a weight loss 9,13745 gr, total acid 0,06798 ml/gr, vitamin C 0,85845 mg/g, and pH value 6,32274